1990
DOI: 10.1002/art.1780330507
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and binding of transforming growth factor β by scleroderma and normal dermal fibroblasts

Abstract: The production and binding of transforming growth factor P (TGFP) were compared in dermal fibroblast tines derived from scleroderma patients and normal control donors. The mean 2 SEM 24-hour level of secretion of TCFP by fibroblast lines derived from the involved skin of scleroderma patients was 30.8 f 5.5 pmoles/106 cells, and it was 29.7 f 5.8 pmoles/106 cells for fibroblast lines derived from the normal skin of the healthy donors. Thus, we found that the fibroblasts themselves produced TGFP. TGFP production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 40 publications
4
28
0
3
Order By: Relevance
“…This cytokine, able to stimulate fibroblasts to produce matrix proteins in vitro, is not involved in our models and seems not to be involved human SSc. Although the data regarding the presence of this cytokine in the skin of SSc patients are contradictory (43,44), it has been clearly shown that fibroblasts from patients with SSc do not secrete more TGF-␤ than normal cells (45). Thus, we believe that we have created a more representative model of human SSc than the bleomycin model.…”
Section: Discussionmentioning
confidence: 94%
“…This cytokine, able to stimulate fibroblasts to produce matrix proteins in vitro, is not involved in our models and seems not to be involved human SSc. Although the data regarding the presence of this cytokine in the skin of SSc patients are contradictory (43,44), it has been clearly shown that fibroblasts from patients with SSc do not secrete more TGF-␤ than normal cells (45). Thus, we believe that we have created a more representative model of human SSc than the bleomycin model.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding scleroderma, it was reported that scleroderma fibroblasts of the involved area did not secrete increased levels of TGF-β1 (16,32). The mechanism of tissue fibrosis in such diseases remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of T␤R expression would result in the deposition of ECM components, which are the chief pathologic features of fibrotic disorders. With respect to SSc, in which progressive fibrosis in the skin is the major cause of the disease, it was reported that scleroderma fibroblasts in the involved area secrete similar levels of TGF-␤1 to normal fibroblasts (22,51). The mechanism of tissue fibrosis in such diseases remains to be determined.…”
Section: Discussionmentioning
confidence: 99%